LANGUAGE LEARNING MOTIVATION EMPLOYED BY THE STUDENTS IN SEKOLAH INDONESIA KUALA LUMPUR, MALAYSIA - Annisa, Riah Khoirul; Hardiyanto, Asep; Sumarno, Sumarno (Premise: Journal of English Education and Applied Linguistics, 2023)
The current article attempts to investigate the motivation of language learning employed by students learning English as a foreign language but living in a state that uses English as a second language, Malaysia. The current research focused on the types of motivation by Gardner & Lambert, namely instrumental and integrative, the dominant types of instrumental and integrative, the differences between natural science and social science, and also what items of students' motivation most related to their language learning. The exploratory, descriptive quantitative method was applied in this study with the total subject (N=18) students of Sekolah Indonesia Kuala Lumpur (SIKL) at XII grade students of natural and social science class categorized into three levels: low, moderate, and high level. A close-ended questionnaire was used, which consisted of fourteen statements adopted from Dornyei's language learning motivation. The study result revealed that in SIKL, students were generally oriented toward instrumental rather than integrative motivation. Both natural and social classes showed that instrumental was more oriented by the students. Furthermore, the students present the motivation to learn English to prepare for a better career and future. Besides, most students present that they are motivated to provide a chance to travel to English countries. The study's findings have implications for the English teaching and learning process, especially for giving good learning materials, methods, and models suitable to their language learning motivation. Furthermore, motivated students tend to put more effort and consistency into their language-learning process, which leads to success.